Avaliação de desempenho de vias do bairro de Batista Campos, em Belém-PA, em relação ao Índice de Condição do Pavimento (ICP) - AIHUKI, Josef Ndauvako (2022)
The Pavement Management System (PMS) must be able to efficiently, prioritize and allocate public resources of its maintenance and rehabilitation program among all sections of the various networks, but in order to determine the future performance of the pavement, it is necessary to know its past performance, over time. Therefore, the main objective of this research is to identify pavement condition index variations within in the neighborhood of Batista Campos between the years 2021 and 2022 and to assess the performance of the pavement. In order to achieve this objective, a field survey was carried out based on the SHRP (Strategic Highway Research Program) method. The pavement grade was acquired by calculating the PCI, which classifies the pavement state from 0 to 100. The obtained results were compared to the previous results, thus allowing an overview of the pavement's condition index variations. The main results were: The average PCI in the neighborhood of Batista Campos reduced from 86.75 to 81.27. The arterial streets in the neighborhood were better preserved than the collector and local streets. The most critical section presented a PCI of 58.33 and the best section presented a PCI of 98.33. The largest reduction in the PCI was (-20.45%). Avenida.16 de Novembro street was the only street to present a positive PCI average variation of + 3,34%. 85.91% of the sections presented a negative PCI variation. São Silvestre street presented the highest negative PCI average variation of (-12.85%). The distresses that evolved the most were corrugations 900%, transverse cracks 162%, fatigue cracks 149% and patches 27%. There was no strong linear correlation between the PCI variation and the elevation of the road. Finally, it is recommended that new assessments be carried out annually, allowing the monitoring of the evolution of the pavement conditions and the pavement deterioration curve.